2009
DOI: 10.1177/0022034509342979
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oral Fibroblast Lifespan Is Telomerase-independent

Abstract: Oral mucosal wound-healing is characterized by rapid re-epithelialization and remodeling, with minimal scar formation. This may be attributed to the distinct phenotypic characteristics of the resident fibroblasts. To test this hypothesis, we investigated patient-matched oral mucosal and skin fibroblasts. Compared with skin fibroblasts, oral mucosal fibroblasts had longer proliferative lifespans, underwent more population doublings, and experienced senescence later, which was directly related to longer telomere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 33 publications
1
27
0
Order By: Relevance
“…Thus, their activity may explain the high-renewal capacity of hOMSC. Recently, Enoch et al [54] reported that OMLP-derived fibroblasts reach 80-115 population doublings before senescence, while donor matched skin fibroblasts only 40-65. This increased self-renewal capacity of OMLP-fibroblasts was telomerase-independent, but was related to increased telomeres length compared with skin fibroblasts suggesting that the OMPL population is endowed with inherent mechanisms that preserves telomere length.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, their activity may explain the high-renewal capacity of hOMSC. Recently, Enoch et al [54] reported that OMLP-derived fibroblasts reach 80-115 population doublings before senescence, while donor matched skin fibroblasts only 40-65. This increased self-renewal capacity of OMLP-fibroblasts was telomerase-independent, but was related to increased telomeres length compared with skin fibroblasts suggesting that the OMPL population is endowed with inherent mechanisms that preserves telomere length.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several studies have shown that fibroblasts isolated from oral mucosa and skin have several inherent phenotypical differences, including a different capability for collagen remodeling, distinct secretion patterns for certain ECM molecules, different growth, migration and cell adhesion properties as well as differential expression of ECM receptors and response to growth factors. Consequently, the phenotype of oral mucosal fibroblasts exhibits similarities to fetal-type fibroblasts that contribute to scar-free healing in fetal skin (7,8,37,168,240,308,(310)(311)(312)(313)(314)(315)(316)(317)(318)(319)(320) (Table 4). These inherent differences may derive from a distinct embryonic developmental program between skin and oral mucosal fibroblasts as the former are derived from mesodermal mesenchymal cells and the latter from cells associated with the neural crest (325).…”
Section: Specific Features Of Oral Mucosal Wound Healingmentioning
confidence: 99%
“…Oral mucosal wounds in rodents that heal faster than skin Results to scar formation Results to minimal scar formation TGF-b1/TGF-b3 isoform ratio higher TGF-b1/TGF-b3 isoform ratio lower Fundamental differences in the expression of MMPs, peptidases, cytokines and chemokines. 1 (7,8,37,168,240,247,273,274,308,(310)(311)(312)(313)(314)(315)(316)(317)(318)(319)(320)(321)(322)(323)(324).…”
Section: Specific Features Of Oral Mucosal Wound Healingmentioning
confidence: 99%
“…The study was undertaken using human normal gingival fibroblasts (hNOF) in situ in order to evaluate biocompatibility of titanium dental implant in contact with the mucosal gingival [16]. However, such hNOF cannot be consistently used for evaluating cytotoxicity of dental products, due to the limited lifespan in serial culture and the genomic instability in later passages [17, 18]. It was studied that the cytotoxicity response of hTERT-hNOF cells is significantly similar to human normal gingival fibroblasts (hNOF) and more sensitive compared to L929 cells with genomic stability even at the later passages [19].…”
Section: Introductionmentioning
confidence: 99%